Synthesize and Characterize Dibutyltin (IV) Oxide Complex by Utilizing New Ligand - Alhaydary, Emad; Yousif, Emad (Al-Nahrain Journal of Science, 2021)
Herein successfully synthesized new organotin (IV) complex Bu2SnOL by reacting sulfamethoxazole drug as a ligand with dibutyltin (IV) oxide. The synthesized complex was fully characterized by Fourier transform infrared, 1proton nuclear magnetic resonance, 13carbon nuclear magnetic resonance, 119tin nuclear magnetic resonance and ultraviolet-visible spectroscopies. Field emission scanning electronic microscopy was also applied to study the surface morphology of synthesized complex. The above techniques have demonstrated that the complex was prepared with high percentage of purity. This type of compound has various applications in medicine and industry. For example, using it as photo–stabilizer of different plastic polymers (polyvinyl chloride, polystyrene and polyvinyl alcohol).